1997
DOI: 10.1073/pnas.94.24.13175
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 9: A candidate gene for asthma

Abstract: Asthma is a complex heritable inf lammatory disorder of the airways associated with clinical signs of atopy and bronchial hyperresponsiveness. Recent studies localized a major gene for asthma to chromosome 5q31-q33 in humans. Thus, this segment of the genome represents a candidate region for genes that determine susceptibility to bronchial hyperresponsiveness and atopy in animal models. Homologs of candidate genes on human chromosome 5q31-q33 are found in four regions in the mouse genome, two on chromosome 18,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(155 citation statements)
references
References 34 publications
4
151
0
Order By: Relevance
“…Among other biological activities (10), it was recently suggested on the basis of genetic linkage analyses that IL-9 might play an important role in the pathogenesis of asthma (18,19). This assumption was supported by the lung-specific expression of IL-9 in transgenic mice, which was accompanied by airway inflammation, bronchial hyper-responsiveness, and mast cell hyperplasia (20) as well as the increased expression of IL-9 and its receptor in human patients with atopic asthma (21).…”
Section: Il-9 and Il-13 Production By Activated Mast Cells Is Stronglmentioning
confidence: 60%
“…Among other biological activities (10), it was recently suggested on the basis of genetic linkage analyses that IL-9 might play an important role in the pathogenesis of asthma (18,19). This assumption was supported by the lung-specific expression of IL-9 in transgenic mice, which was accompanied by airway inflammation, bronchial hyper-responsiveness, and mast cell hyperplasia (20) as well as the increased expression of IL-9 and its receptor in human patients with atopic asthma (21).…”
Section: Il-9 and Il-13 Production By Activated Mast Cells Is Stronglmentioning
confidence: 60%
“…RC strains are a powerful tool to unravel the genetics of genetically complex processes as it allows mapping of the genes involved. For example, Nicolaides et al 45 could identify IL-9 as a quantitative trait locus implicated in the normal airway response to acetylcholine. Also, the CcS/ Dem strains, which were also used in our experiments, have already been successfully used by different groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice have shown association of differences in expression of IL9 gene with biological variability in bronchial responsiveness. 18,19 In humans, IL9 was found to influence chemokine release from bronchial epithelial cell 20,21 and airway smooth muscle, 22 and has also been shown to induce goblet cell hyperplasia during repair of human airway epithelia. 23 This pleiotropic effect of IL9 is in agreement with our findings.…”
Section: Sex-specific Qtl Underlying Asthma Phenotypes H Aschard Et Almentioning
confidence: 99%